Long-term effect of patient decision aids on use of joint replacement and health care costs. Issue 6 (June 2020) - Trenaman, L.; Stacey, D.; Bryan, S.; Payne, K.; Hawker, G.; Bansback, N.
Summary: Objective: Shared decision-making supported by patient decisions aids may improve care and reduce healthcare costs for persons considering total joint replacement. Observational studies and randomized controlled trials (RCTs) have evaluated the short-term impact of decision aids on uptake of surgery and costs, however the long-term effects are unclear. This analysis aimed to evaluate the effect of patient decision aids on 1) use of joint replacement up to 7-years of follow-up, and 2) osteoarthritis-related health system costs. Methods: 324 participants in a Canadian RCT with 2-years follow-up who were randomized to either a decision aid ( n = 161) or usual care ( n = 163) had their trial and health administrative data linked. The proportion undergoing surgery up to 7-years were compared using cumulative incidence plots and competing risk regression. Mean per-patient costs were compared using two sample t -tests. Results: At 2-years, 119 of 161 (73.9%) patients in the decision aid arm and 129 of 163 (79.1%) patients in the usual care arm had surgery. Between two and 7-years, 17 additional patients in both the decision aid (of 42, 40.4%) and usual care (of 34, 50.0%) arms underwent surgery. At 7-years, patients exposed to decision aids had a similar likelihood of undergoing surgery (HR = 0.92, 95% CI:0.73 to 1.17, p = 0.49) and mean per-patient costs (21, 965 vs 23, 681, incremental cost: -1, 717, 95% CI:-5, 631 to 2, 198) compared to those in usual care. Conclusions: This is the first study to assess the long-term impact of decision aids on use of joint replacement and healthcare costs. These results are not conclusive but can inform future trial design. Clinical trial registration: The full trial protocol is available at ClinicalTrials.Gov (NCT00911638 ).